Methanol electrolysis for hydrogen generation in PEM electrolyser - Chern, Alexander Wei Wen (2014)
Hydrogen is used in many applications as an exceptional source of fuel due to its high heating value. In comparison to water electrolysis, methanol-water electrolysis requires a much lower voltage to initiate reaction. Recent studies include new technology involving proton exchange membrane fuel cells (PEMFC) which use a polymer membrane to separate the anode from the cathode and only allows protons to pass through. This innovation has given rise to many benefits including being able to produce nearly pure hydrogen under pressure as well as reduced environmental effects. This paper reports the efficient production of hydrogen gas via electrolysis of methanol-water solution in a proton exchange membrane electrolyser consisting of a Pt-Ru/C catalyst on the anode and Pt/C catalyst on the cathode side. Various experimental parameters such as methanol concentration, cell voltage, cell temperature, membrane thickness, and catalyst loading were investigated for their effect on hydrogen production. Results show that high temperatures improve performance across all experiments due to increased reaction rate and kinetics. Results also show that thicker membranes produce much better results at higher temperatures. This could be because at high temperatures methanol crossover occurs much more than at lower temperatures. Due to the fact that thicker membranes have higher resistance to methanol crossover, it makes sense that thicker membranes perform better at higher temperatures. The best performance gave a peak current density of 230mA/cm2 at a voltage of 0.5V, using Nafion-117 (N117) membrane, with a catalyst loading of 1.5mg/cm2 Pt-Ru/C (40wt% Pt, 20wt% Ru, supported on carbon black), at a temperature of 80°C and methanol concentration of 3M. The results indicate high performance under the conditions which shows the suitability and attractiveness of methanol as a fuel source for distributed hydrogen production.